2004
DOI: 10.1080/15287390490443731
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorines Affect the Steroid Hormone Cortisol in Free-Ranging Polar Bears (Ursus maritimus) at Svalbard, Norway

Abstract: Since the polar bear (Ursus maritimus) is among the most highly organochlorine-contaminated species of the Arctic mammals, there is growing concern that in addition to the natural stressors in the polar bear's environment, several organochlorines (OCs) may be able to change basic endocrine pathways. Alterations in the hypothalamic-pituitary-adrenal (HPA) axis may affect plasma cortisol concentrations and inhibit physiological processes involved in the maintenance of homeostasis in a way that may endanger the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 87 publications
(89 reference statements)
2
57
1
Order By: Relevance
“…An unexpected outcome of our study was that the 1 mg/kg PCB group vocalized significantly less than the control and 0.1 mg/kg groups, suggestive of a decreased stress response. PCBs are associated with decreased glucocorticoid levels in rat (Durham and Brouwer, 1990), a human in situ system (Li and Wang, 2005), an (Love et al, 2003), polar bears (Oskam et al, 2004) and rainbow trout (Aluru and Vijayan, 2006). Our results suggest that A1221 may be decreasing stress responsiveness in the 1 mg/kg exposed females.…”
mentioning
confidence: 54%
“…An unexpected outcome of our study was that the 1 mg/kg PCB group vocalized significantly less than the control and 0.1 mg/kg groups, suggestive of a decreased stress response. PCBs are associated with decreased glucocorticoid levels in rat (Durham and Brouwer, 1990), a human in situ system (Li and Wang, 2005), an (Love et al, 2003), polar bears (Oskam et al, 2004) and rainbow trout (Aluru and Vijayan, 2006). Our results suggest that A1221 may be decreasing stress responsiveness in the 1 mg/kg exposed females.…”
mentioning
confidence: 54%
“…Differences were noted between sexes only for the innermost blubber layer; however, the small sample size for females precludes a complete assessment of the influence of sex on cortisol. Results in the literature regarding sex differences in cortisol are mixed in marine and terrestrial mammals, with some documenting differences among sexes in polar bears (Oskam et al 2004;Macbeth et al 2012) whereas others found no differences in polar bears, grizzly bears, and harbour porpoises (Eskesen et al 2009;Macbeth et al 2010;Bechshoft et al 2013). The higher cortisol levels in the metabolically active inner blubber layer of females compared to males may be a reflection of higher stress conditions or energetic demands in reproductive females (Macbeth et al 2012 and references therein).…”
Section: Cortisol Levels and Variabilitymentioning
confidence: 98%
“…Studies dealing with the effects of CHCs on polar bear health have raised significant concerns. As recently summarized by Fisk et al (2005-this issue), the current understanding of contaminant-induced biological effects in polar bears points to evidence that chronic exposure to CHCs and their metabolites may compromise endocrine functions and homeostasis (Sandau, 2000;Norstrom, 2000;Skaare et al, 2001a;Letcher et al, 2002;Haave et al, 2003;Oskam et al, 2003Oskam et al, , 2004Braathen et al, 2004), immune functions (Bernhoft et al, 2000;Norstrom, 2000Norstrom, , 2001Skaare et al, 2001b;Larsen et al, 2002;Lie et al, 2004aLie et al, , 2005Kirkegaard et al, 2005), cub and reproductive female survival , reproduction and development (Wiig et al, 1998), and hepatic P450-enzymes induction (Bandiera et al, 1995;Letcher et al, 1996).…”
Section: Introductionmentioning
confidence: 99%